Reduction of Ammonia Emissions from Laying Hen Manure in a Closed Composting Process Using Gas-Permeable Membrane Technology - María Soto-Herranz; Mercedes Sánchez-Báscones; Juan Manuel Antolín-Rodríguez; Pablo Martín-Ramos (Agronomy, 2021)
Nitrogen losses during composting processes lead to emissions problems and reduce the compost fertilizer value. Gas-permeable membranes (GPM) are a promising approach to address the challenge of reducing nitrogen losses in composting processes. This study investigated the applicability of two GPM membrane systems to recover N released during the closed composting process of laying hen manure. The ammonia (NH3) capture process was performed using two different systems over a period of 44 days: the first system (S1) consisted of 120 m of an expanded polytetrafluoroethylene (ePTFE) membrane installed inside a 3.7 m3 portable, closed aerobic composter with forced ventilation; the second system (S2) consisted of 474 m of an ePTFE membrane placed inside as an external module designed for NH3 capture, connected to a closed aerobic composter through a pipe. In both cases, a 1 N H2SO4 acidic NH3 capture solution was circulated inside the membranes at a flow rate of 2.1 L·h−1. The amount of total ammonia nitrogen (TAN) recovered was similar in the two systems (0.61 kg in S1 and 0.65 kg in S2) due to the chosen membrane surface areas, but the TAN recovery rate was six times higher in system S1 (6.9 g TAN·m−2·day−1) than in system S2 (1.9 g TAN·m−2·day−1) due to the presence of a higher NH3 concentration in the air in contact with the membrane. Given that the NH3 concentration in the atmosphere of the membrane compartment directly influences the NH3 capture, better performance of the GPM recovery system may be attained by installing it directly inside the closed aerobic composters. Regardless of the chosen configuration, this technology allows N recovery as a stable and concentrated 1.4% N ammonium salt solution, which can be used for fertigation. The presented GPM systems may be used in community composting systems with low volumes of waste to be treated or in livestock facilities that have implemented best available techniques such as solid–liquid separation or anaerobic digestion, provided that the use of GPM technology in combination with these techniques also contributes to odor mitigation and improves biogas yields.